ANALISIS RISIKO KETERLAMBATAN PELAKSANAAN PROYEK KONSTRUKSI HOTEL DI BALI - Karyawan Salain, I Made Alit; Dharmayanti, G. A. P. Candra; Anindita, Gde Ngurah (JURNAL SPEKTRAN; Vol 7 No 2 (2019): Vol. 7 No. 2, JULI 2019, 2019)
RISK ANALYSIS OF THE CONSTRUCTION PROJECT DELAY OF HOTEL IN BALI ABSTRACT Hotel construction projects generally have a high level of complexity compared to other building construction projects, because of the many jobs that must be integrated with each other and have a tight work schedule. All of that has the potential to cause delays in the implementation of construction projects for hotel projects in Bali. This study aims to analyze the risk of delays in implementing hotel construction projects in Bali.This study uses a qualitative descriptive method with primary data sources taken through surveys using a questionnaire. Respondents were taken based on purposive sampling method which was selected based on criteria that respondents played an important role in hotel construction projects in Bali, as many as 35 respondents, which included one director, one project manager; one site manager, two supervisors; two quality control. The results showed that there were 44 risks of delays in hotel construction projects in Bali consisting of 37 major risks and 7 minor risks. Major risks included 22 undesirable risks with 36 mitigation actions, and 15 unacceptable risks (unacceptable risks) with 24 mitigation measures. Risk related to project was indicated as frequently found the source of risk. Project risk at unacceptable risk is the determination of a very tight schedule, a work plan that is not well structured and changeable, understanding the rules of work drawings, resource mobilization, unavailability of materials as needed. Risk related to project that categorized as undesirable covered: limited authority of personnel/owners in decision making, inspection methods and job control by the owner, failure of the owner to coordinate work with the contractor, inadequate provision of tools/materials by the owner, inadequate number of workers, and inadequate work equipment. Mitigation measures are emphasized on project risk and technical risk including the preparation of detailed and comprehensive planning and scheduling, attention to work documents and contracts, as well as improving coordination between relevant parties and also optimizing the accuracy of plans in carrying out the work